PENGARUH PENGGUNAAN TEPUNG KUNYIT ( Curcuma domestica Val.) DAN LAMA PENYIMPANAN TERHADAP KUALITAS SOSIS IKAN TENGGIRI (Scomberomorus sp) - Syaifuddin (Jurnal Pengolahan Pangan, 2019)
This study aims to determine the effect of giving levels of turmeric flour and storage time on microbiological quality, sensory quality and chemical quality of mackerel fish sausages. The method used in this research is descriptive research used to observe the total number of bacterial colonies and molds, while experimental research using Factorial randomized block design (RBD) for analyzing sensory tests. Completely Randomized Design (CRD) factorial pattern for analyzing water content and pH tests. The results showed the administration of turmeric flour can inhibit bacteria and mold for 12 hours. Sensory testing showed an interaction between the level of turmeric flour treatment and storage time. Chemical testing shows the storage time can cause fluctuations in water content. The pH test shows the level of turmeric flour can increase the pH value, and the pH value will decrease during storage. The conclusion of the study is that the level of turmeric flour and storage time affect the quality of sausage microbes. The interaction between the level of turmeric flour and the length of storage has an influence on the taste and texture of fish sausages during storage by inhibiting the growth of microbes so as to maintain quality degradation. levels of turmeric flour and storage duration affect the chemical quality of sausages